A Pd NP-confined novel covalent organic polymer for catalytic applications. (6th January 2020) - Yadav, Deepika; Awasthi, Satish Kumar
Abstract : A novel unsymmetrical covalent organic polymer was synthesized via nucleophilic substitution reaction of 2, 4, 6-trichloro-1, 3, 5-triazine with p -amino phenol. Abstract : A novel unsymmetrical covalent organic polymer, COP (1 ), was designed and characterized using several analytical and spectroscopic techniques. COP (1 ) was synthesized via the nucleophilic substitution reaction of 2, 4, 6-trichloro-1, 3, 5-triazine with p -amino phenol. Subsequently, COP (1 ) was immobilized with Pd(0) on its exterior and utilized as a heterogeneous catalyst (Pd@1 ). Pd@1 exhibited excellent catalytic activity and reusability for the Sonogashira C–C cross coupling reaction, and a few new products were synthesized. The confinement of Pd was well supported by the suitable functionalities present on the surface of COP (1 ). Furthermore, Pd@1 was used for eight consecutive catalytic runs without any considerable loss in its activity and no leaching of the metal NPs was observed.